Loan and bond finance in Argentina, 1985-2005 - Roque B. Fernández; Celeste González; Sergio Pernice; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
Loan and bond finance during 1985-2005 can be divided into three sub-periods. After the 1982 debt crisis, which mainly involved domestic and foreign bank loans to both the corporate and government sectors, there was practically no credit. This situation of lack of credit persisted until the domestic economy was stabilized in 1991 with the Convertibility Plan, and foreign debt renegotiation was completed in 1993 with the Brady Plan. Loan finance recovered to unprecedented levels since the 1950s, and bond finance became for the first time an important financing vehicle for both the national government and large firms in the corporate sector. Credit came to a sudden stop in 2001, with widespread default on both corporate and government bonds. The 2001 debt crisis was not followed by runaway domestic inflation, and by 2005 Argentina was able to return to foreign capital markets.
Keywords: G1; H6; 330; bank loans; sovereign bonds; provincial bonds; central bank bonds; corporate bonds; pension funds; yields; liquidity; Finanzmarkt; Anleihe; Argentinien